The Formation of Pan-Indian Communities Among Hindus and Muslims: 19th Century Evolution. - Khullakpam Sharif; Dr J. Muthukumar; Faheem Ahmad Dar (RADJA PUBLIKA, 2025)
Essentially, India's shift towards modernity disrupted traditional localities, marking the onset of a broader political mobilisation among Hindu and Muslim communities. The social reform movement, which later crystallised into a pan-religious movement among Hindus and Muslims, shaped 19th-century India. Various factors have contributed to this movement. The British rule in India is one important factor that helped in triggering the movement leading to the growth of communal tension between the Muslims and Hindus. The formation of pan-Indian communities is not just a passive process; it is also perceived as a deliberate project undertaken by various people, including the different religious groups. This deliberate effort contributed to the development of a ‘perception of crisis’ that necessitated intentional actions, ultimately leading to the emergence of pan-Indian communities among the Hindus and the Muslims. The promotion of Hindi as the medium of instruction in government schools and colleges, along with cow protection and anti-Ahmadiya propaganda among Hindus, coincided with a new evolution marked by conflict between fundamentalists and revivalists among Muslims. Later, this process raises the question of the arrival of a new ideology known as ‘communalism’, with communal riots being just one of the outcomes of the propagation of this ideology. This research article will give an overview of the formation of Pan-Indian communities among Hindus and Muslims and its evolution in the 19th century.